Hormonal induction of males as a method for studying tropical cladocerans: description of males of four chydorid species (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y.; Sanoamuang, La-Orsri (Zootaxa, 2011)
Methyl farnesoate, a crustacean juvenile hormone, successfully induced male development in several littoral cladocerans from Thailand in short-term multispecies cultures. Male morphology is fully described in four species of Chydoridae— Oxyurella singalensis Daday, 1898, Leberis diaphanus (King, 1853), Leydigia cf. ciliata Gauthier, 1939, Disparalona cf. hamata (Birge, 1910). Males of the latter two taxa from Thailand differ from these from the other localities, suggesting the presence of sibling-species in the Indochina region.